If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Simplifying 23x + 1 = 5 Reorder the terms: 1 + 23x = 5 Solving 1 + 23x = 5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + 23x = 5 + -1 Combine like terms: 1 + -1 = 0 0 + 23x = 5 + -1 23x = 5 + -1 Combine like terms: 5 + -1 = 4 23x = 4 Divide each side by '23'. x = 0.1739130435 Simplifying x = 0.1739130435

| 5r-6r=-3 | | -1=d4-7 | | 3ln(x+3)=0.7x+2 | | 24=4r+4r-12 | | 15b^2+32b+7=-9 | | 250x+18000=700x | | (m+4)-5m= | | 18000x+250=700x | | a+8=20 | | 10y^4+29y^2+21=0 | | 5y^2+4=-21y | | 15x+54000=18x | | 3[x+(-2)]-2=-1 | | 7+3x=5x+5 | | 30+5a=22 | | 4(x-3)=x | | K-4.8=-7.2 | | 1.5x+3200=1.7x | | (3u-5)(4+u)=0 | | -5x+4=-7 | | 14x+32000=16x | | 15=-6+f | | -3x-2=-10 | | 2x+5=3(4x-5) | | -2x+5=4 | | 3(4k+14)=10k-12(k-7) | | -3x+2=3 | | 21=y+4 | | 6x+5=4x+1312 | | 4*z=36 | | 8x+3=7x | | (8+z)(3z+5)=0 | | 9+3(4x-5)=12-2(x+30) | | -4x+3y=-11 | | 5(2x+3)=215 | | 2x^2-7x=9 | | 24+2(x+4)=2(x+3) | | 3x-x=-27-19 | | 60-5Y=30 | | 14x+9y=26 | | 288-3x=42x+23 | | -6/2.3=n | | 11x^2+7x-4=0 | | 42/18=n | | 18/42=n | | 6-1/4=8+t/2 | | 4x-5+(x+2)(8x-10)=0 | | 6X-50=30 | | -11-4x=7-4x | | 3a-8=a/2+2 | | 9-4/5(u-3)=1 | | -x+5=-4x-71 | | x-5=29 | | 3a-a/2=8+2 | | 3x^2-2x+1=4 | | 17=-3+5x | | 3/9=n | | 9/3=n | | -5y+5=5y-15 | | 2x^2-x=x^2+2x+40 | | 4x^2-13x+8=-4x+3 | | 0.1x-2=-2.4 | | 4y+3/7=9 | | 6(2n+4)=8(5n+1)+4 | | -5y-3=-4y-13 |

- Equations solver - equations involving one unknown
- Quadratic equations solver
- Percentage Calculator - Step by step
- Derivative calculator - step by step
- Graphs of functions
- Factorization
- Greatest Common Factor
- Least Common Multiple
- System of equations - step by step solver
- Fractions calculator - step by step
- Theory in mathematics
- Roman numerals conversion